Otto Said that I am a Fool: Sententialism, Indexicals and Kaplanian Monsters. (2nd March 2021) - Felappi, Giulia
Abstract: According to sententialism, 'Otto said that I am a fool' expresses the holding of a relation between Otto and the sentence 'I am a fool'. Sententialism is generally considered doomed, but I will show that a suitably developed sententialist account can surmount the many objections that have been raised. I will also show how important it is to have a fairer attitude towards sententialism. For if sententialist accounts are recognised as real options, it should also be recognised that the conclusion, drawn by many, that sentences such as the report above force us to introduce Kaplanian monsters is unwarranted.